Underutilised Oyster Nut (Telfairia pedata): Farmers’ Knowledge, Practices and Utilisation in Northern Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Oyster nut [Telfairia pedata (Smiths ex Sim)] Hook is a regularly cultivated crop in East African countries such as Tanzania (including Zanzibar Island), Uganda, Angola, Mozambique, and along Kenya’s coast, which is regarded to be underutilised. Despite its relevance to small-scale farmers in terms of conservation, income creation and food security, little is known about the farmer’s knowledge, practices and utilisation in Northern Tanzania. Therefore, this study aimed at investigating aspects of its production, including farmers’ practices, utilisation and preferences. Data collection was carried out through semi-structured questionnaires in the regions of Arusha, Kilimanjaro and Tanga. Descriptive analysis was done whereby frequencies, means and percentages were calculated using SPSS from the farmers’ responses. The results on oyster nut preferences, knowledge, cultivation and utilisation were presented in the form of tables and graphs. The findings revealed that 87% of respondents who were knowledgeable about oyster nuts were female, 89% of interviewed farmers grew the nuts on inherited family lands, 24% of respondents stored oyster nuts in perforated plastic bags, and 90% of the farmers used recycled seeds as their primary method of propagation without the use of any agricultural inputs. Conclusively, the study gives significant baseline data for future research on oyster nuts and development projects in Tanzania to enhance its conservation and sustainable usage while ensuring nutritional security for the majority of resource-poor people.